POLA MOTIF CERITA ASAL-USUL RAJA PERTAMA DALAM LEGENDA MUNA, WOLIO, DAN TOLAKI - Mustafa Husba, Zakiyah; Aso, La; Ibrahim, Irianto (Universitas Halu Oleo, 2021)
In an effort to reveal the structure of the motifs in the legend stories of the origins of the first king as a step in obtaining historical and cultural knowledge of But and Tolaki ethnic communities, it is hoped that this research can be a frame of reference for the protection and development of Southeast Sulawesi regional literature. The purpose of this study is to describe Â patterning of the motifs of the origin story of the first king from the legends of Muna, Wolio, and Tolaki. This research is based on the motive theory of Alan Dundes. Motive theory is used to find the class of motives for each item or sequence of events in the story. The patterns of motifs in the form of tables and schemes are arranged based on the Stith Thompson index motifs. The method used in this research is qualitative method. Data collection techniques with library reading and note-taking techniques, as well as recording and note-taking interview techniques. The data processing is done by triangulation technique. The research data was examined using qualitative descriptive techniques through 2 stages, namely indexing motifs and patterning motifs. The results of the analysis show that there are 9 motifs in the three stories, mythological motifs, magic, other worlds, wise and foolish, restoration of fate, society, natural cruelty, and sex motives. Furthermore, 4 dominant motifs or the same motif are found in the 3 stories of the first kings of Muna, Wolio, and Tolaki, namely mythological motifs, other worlds, wise and foolish, and society motifs.Keywords: motif, legend, Muna, Wolio, and Tolaki